Native Gold as a Specific Indicator Mineral for Gold Deposits - Palyanova, Galina (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue reprint includes one review and fifteen research articles. The review by Palyanova et al. (2023) summarized the available information on the palladian gold and proposed classifying the types of deposits based on the fineness, content, and set of impurities in palladian gold and minerals intergrown with it. Fifteen articles focused on the typomorphic features of native gold from gold deposits in Russia, India, Chile, Scotland, and Canada. This Special Issue aims to identify and generalize the reasons for variations in the compositions of native gold. I hope all the articles in this Special Issue will be helpful and valuable resources for anyone who is interested in native gold and gold deposits. I thank the Authors and Reviewers for their efforts and contributions. I am also grateful to the Editor-in-Chief, Editors and Assistant Editors of Minerals for their help.